(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
This study explains how the pyrimidinyloxybenzoic herbicide Bispyribac sodium can be brokendown by sunlight and other sources, making it safer for use in paddy fields. ZnONa2S2O8 was studied as aphoto sensitizer oxidant in an aqueous suspension to determine its degradation. Bispyribac sodiumphotocatalysis was investigated in daylight using three different aqueous buffer solutions (pH 4, 7, and9). We also looked into how bispyribac sodium and its metabolites impacted green algal development inthis study (Pseudokirchneriella subcapitata). When compared to photolysis experiments, the resultsdemonstrated that the inclusion of a photosensitizer significantly improved pesticide removal. Thismethod also rapidly increases the reaction rate. Compared to using just ZnO, the addition of the oxidant(Na2S2O8) speeds up the reaction and provides additional benefits. Degradation of sodium bispyribacoccurs with first-order kinetics. Statistics were used to calculate green alga growth rates (Er) and yieldpercentages (Ey). There was a significant decrease in growth rate inhibition with increasing irradiationtime.